Foreign Policy Analysis in a Changing Context: An Approach - Murillo-Zamora, Carlos (2023)
The foreign policy constitutes a particular field of study, attracting the attention of academics and research centers due to its intermestic nature (formulated in the internal or domestic sphere and implemented in the international or external sphere) and because it results from the contributions of International Relations, Political Science and Public Administration. Thus, it constitutes a bridge discipline of International Relations. In addition, its definition and characterization are complex since depend on how the State that formulates and implements it perceives itself; but also, because it relies on the type of State actor in question. A great power is not the same as a small State; necessary to highlight more than three-quarters of the countries in the international system are small agents. For this reason, since the mid-twentieth century, the interest of international analysts has focused on this field. In the same way, the analysis of foreign policy, as a research space, has shown an important evolution, requiring novel approaches and methodologies. On the other hand, the changes in the international system, particularly the end of the Cold War and the attacks of the so-called 9-11, introduced variants in the approach to this issue. However, it was with the SARS-CoV-2 pandemic and the war in Ukraine that reality has become more complex and demands new perspectives for analyzing foreign policy, especially of great powers and small states. Then, this article reviews the main texts on foreign policy, from the mid-last century and up to what was published this year (2023). The intention is to offer a sort of state-ofthe-art, for those who are interested in dabbling in the analysis of foreign policy and identifying the main ideas and approaches for subsequent research work